2006
DOI: 10.1523/jneurosci.4636-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid-Related Orphan Receptor α Controls the Early Steps of Purkinje Cell Dendritic Differentiation

Abstract: Dendritic differentiation involves both regressive and growth events. The mechanisms controlling the regressive events are poorly understood. This study is aimed at determining the role of the nuclear receptor retinoid-related orphan receptor ␣ (ROR␣) in Purkinje cell (PC) dendritic differentiation in organotypic cultures. As observed in vivo, in these cultures, fusiform PCs with embryonic bipolar shape undergo regression before the outgrowth of the ultimate dendritic tree. We show that lentiviral-mediated hRO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 59 publications
7
83
0
Order By: Relevance
“…5A) (Kapfhammer, 2004). We first observed that, as previously described in the mouse (Boukhtouche et al, 2006), rat PCs in organotypic slices cultured at P0 are bipolar and fusiform (stage 1) during the very first days in vitro (div). This stage corresponds to the early fusiform stage described in vivo (Ramó n y Cajal, 1926;Armengol and Sotelo, 1991).…”
Section: Sclip Is Strongly Expressed In Developing Purkinje Cells In mentioning
confidence: 63%
See 4 more Smart Citations
“…5A) (Kapfhammer, 2004). We first observed that, as previously described in the mouse (Boukhtouche et al, 2006), rat PCs in organotypic slices cultured at P0 are bipolar and fusiform (stage 1) during the very first days in vitro (div). This stage corresponds to the early fusiform stage described in vivo (Ramó n y Cajal, 1926;Armengol and Sotelo, 1991).…”
Section: Sclip Is Strongly Expressed In Developing Purkinje Cells In mentioning
confidence: 63%
“…Indeed, the large majority of transduced cells infected at P0 are PCs (Fig. 4A) (Boukhtouche et al, 2006). Furthermore, the neighboring untransduced PCs within the same cellular environment are not affected, and exhibit a normal morphology with protrusions at stage 2 and dendritic processes at stages 3 and 4.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations